EFFECT OF POLLUTION DUE TO COCONUT HUSK RETTING ON THE SPECIES DIVERSITY OF BENTHIC COMMUNITIES OF COCHIN BACKWATERS - Devi, M Ambika; Pillai, N Gopakalakrishna (Indian Journal of Fisheries, 2011)
The variation in abundance, distribution, biomass and species diversity of benthic communities of aretting zone was studied in comparison with that of a non-retting area. The distribution patterns ofbenthic population was essentially controlled by the hydrographic changes produced as a result of retting.The population density and the species diversity of the benthic faiua were low in the retting zone whilea higher species diversity and density were otecrved in the marginal and dean zones. The reductionin the population of the retting ground was the adverse effect of decades of retting activity and the consequentpollution of the region by the retting Icachlcts.